Rethinking “Decoloniality and Futurity” for the Anthropocene: A Speculative Spectrality - Rangga Kala Mahaswa (Digital Press Social Sciences and Humanities, 2023)
What is this thing called the Anthropocene? The Anthropocene is a strange thing. It is interesting conceptually, fascinating scientifically, and critically intriguing for our understanding when experiencing the borderless uncanny world-earth meeting. If an ontological uncanny of natural crisis time represents the promise of [M]odernity, which civilisation has altered nature, even colonised Earth into terra incognita circumstances and catastrophic possibilities simultaneously. The word ‘decolonisation’ of Anthropocene means ignoring the role of the world-colonialism system and creating the worlding conditions after modernity progress. However, the objections of the Anthropocene do not separate calamities based on ideology, political movement, social class, cultural local-wisdom, or even philosophical doctrine. In the eye of a geological epoch, human is being objects at the same time. For example, after the Great Acceleration event, people unconsciously produced a new planetary risk through rapid uncontrolled population growth, advanced post-capitalism industrialisation, and other unseen anthropogenic activities. Should [All] Humans be responsible for mass extinction and be wise in adapting near planetary future? The answer is open-ended because all of us are always possible contributors to anthropogenic wastes, even in small amounts, as non-neutrality accumulation. So, we cannot really hide in the image of the decolonisation of the Anthropocene, although it challenges Western thought categories about geophysical force and geopolitical agents in postcolonial view. It has never been (geo) decolonised—dwelling on the Earth—but we are only possible to decolonise our humanity. The limitation of our perception grasps the real-uncertainty-materiality world, breaking the wall of narcissistic self-exceptionalism. Conceptually, decentering subject helps us feel the strangeness of non-human entities, opening a more-than-human possible world. Additionally, (re)questioning the status of ‘Anthropos’ in the Anthropocene is critically important to remind us that it is part of our concern to consider the prospect of new interrelations between human and non-human. To do so, the recent revival of new weird materialism and speculative turn can open up the context of agency and materiality in the global Anthropocene.